Implementing dengue hemorrhagic fever epidemiological investigation during the COVID-19 pandemic - Kamilia, Nadiyah (BKM Public Health and Community Medicine, 2021)
Objective: Dengue epidemiological investigation studies dengue transmission, including activities to search for cases or suspected cases of dengue infection as well as inspection of dengue-transmitting mosquito larvae in the patient's residence and surrounding buildings within a radius of at least 100 meters. This study describes the implementation of an epidemiological investigation of Dengue Hemorrhagic Fever during the Covid-19 pandemic. Methods: This study used a descriptive method conducted from field observations during January – September 2021. Data collection was carried out at the Health Office level with one person Dengue data manager and 18 Dengue program holders in Gunungkidul Regency. Results: Sixty confirmed DHF cases were reported by hospitals and clinics, 21 cases (35%) were not investigated for epidemiology, Median age of PE officers was 44 years (range: 31-52) where there are more male officers than female officers (63%). Using PPE during PE (100%), visiting neighbors' houses (42%), NS-1 screening (0%), larva monitoring (100%), ABATE distribution (85%), and counseling (100%). In 2020, there was never a recorded case of Dengue Hemorrhagic Fever that did not carry out an epidemiological investigation. This obstacle also hampered the Dengue surveillance system in the district. Conclusion: The Covid-19 pandemic has hampered the epidemiological investigation of Dengue Hemorrhagic Fever. Workers did not conduct. There is a need for a strategy to continue to carry out epidemiological investigations in this situation. Keywords: Epidemiological Investigations, Covid-19 Pandemic, Dengue Hemorrhagic Fever Objektif : Penyelidikan Epidemiologi (PE) Dengue adalah upaya penyelidikan fokus penularan penyakit Dengue meliputi kegiatan pencarian adanya kasus atau suspek infeksi Dengue serta pemeriksaan jentik nyamuk penular Dengue di tempat tinggal penderita dan bangunan sekitar dalam radius sekurang-kurangnya 100 meter. Penelitian ini bertujuan untuk menggambarkan pelaksanaan penyelidikan epidemiologi Demam Berdarah Dengue yang berlangsung selama pandemi Covid-19 di Kabupaten Gunungkidul. Metode : Penelitian ini menggunakan metode deskriptif yang dilakukan dari pengamatan lapangan selama Januari – September 2021. Pengambilan data dilakukan di level Dinas Kesehatan dengan 1 orang data manager Dengue dan 18 orang pemegang program Dengue di Kabupaten Gunungkidul. Hasil : Sebanyak 60 kasus konfirmasi Demam Berdarah Dengue yang dilaporkan oleh Rumah sakit dan klinik , 21 kasus (35%) tidak dilakukan penyelidikan epidemiologi , Median usia petugas PE adalah 44 tahun (range : 31-52) dimana petugas laki-laki lebih banyak dari petugas perempuan (63%). Menggunakan APD saat PE (100%), kunjungan rumah tetangga ( 42%), Screening NS-1 (0%), pemantauan jentik (100%), pembagian ABATE (85%), dan penyuluhan (100%). Pada tahun 2020 tidak pernah tercatat kasus Demam Berdarah Dengue yang tidak dilakukan penyelidikan epidemiologi sehingga hambatan ini juga menghambat sistem surveilans Dengue di Kabupaten Gunungkidul. Kesimpulan : Pandemi Covid-19 menghambat pelaksanaan penyelidikan epidemiologi Demam Berdarah Dengue di Kabupaten Gunungkidul, adapun pelaksanaan penyelidikan epidemiologi tidak melakukan kunjungan rumah sekitar penderita. Perlu adanya strategi untuk tetap melakukan penyelidikan epidemiologi di situasi ini. Kata Kunci : Penyelidikan Epidemiologi, Pandemi Covid-19, Demam Berdarah Dengue